Does the age, income and food expenditure of pregnant have an impact on the incidence of chronic energy deficiency - Amaliah, Fitri; Salam, Abdul; Virani, Devintha (Community Research of Epidemiology (CORE), 2021)
Chronic Energy Deficiency (CED) is the poor nutritional status of a person is caused by the lack of consumption of food sources of energy that contain macronutrients that lasts long or years. CED in pregnant women will cause problems for both mother and fetus. There are several factors that can cause CED in pregnant women including age, family income, food expenditure, etc. This study aims to determine the relationship age, family income, and food expenditure with CED in pregnant women in Makassar city on 2020. This study was conducted on 104 people. To detect CED in pregnant women by measuring the mid upper arm circumference (MUAC) using MUAC ribbon. Age, family income, and food expenditure are measured using questionnaires of modification from national social economic survey on 2017, and univariate analyses and bivariates using SPSS 24. The results of the study showed the relation of age with CED in pregnant women obtained significant value (p value = 0,305), relation of family income with CED in pregnant women obtained significant value (p value = 0,270), and relation of food expenditure with CED in pregnant women obtained significant value (p value = 0,452). There aren’t relationship age, family income, and food expenditure with CED in pregnant women in Makassar city on 2020.